Early indications that low mental quality of life scores in recently unwell older people predict downstream functional decline - Atlas A (Dove Medical Press, 2015)
Alvin Atlas, Karen Grimmer, Kate Kennedy International Centre for Allied Health Evidence, University of South Australia, Adelaide, SA, Australia Background: Accurately detecting markers of early functional decline (FD) are essential to support older people to successfully age in place; however, these markers are poorly understood. We tested the hypothesis that compromised mental quality of life after a minor health crisis could be an early predictor of FD.Methods: This longitudinal observational cohort study was conducted in the emergency department (ED) of a large Australian hospital and in the community. Data were collected from 148 community-dwelling people aged 65+ years, who provided data at recruitment (baseline), and at 1 month and 3 months post discharge from the ED. Short Form-12 mental quality of life component scores (MCS) were regressed with patient descriptors taken at baseline (age, sex, socioeconomic status, education, Mini-Mental State Examination, and primary language), and over-time estimates of FD taken at baseline, and at 1 and 3 months post discharge (instrumental activities of daily living, frequency of falls and hospitalizations, use of gait aids, receipt of community services, living status, and requiring a carer).Results: MCS at 1 month (MCS1) post ED discharge was significantly associated with instrumental activities of daily living at 1 (r=0.45, P<0.001) and 3 months (r=0.401, P=0.001) post ED discharge, but not at baseline (r=0.010, P>0.05). Subjects with lower than the population median MCS showed a significant linear decline in total instrumental activities of daily living scores over 3 months (P=0.025). There was no linear trend over time in the relationship between MCS1 with frequency of falls (P=0.20) or hospitalizations (P=0.42); however, there was a significant difference at 3 months post ED discharge for falls (P=0.036) and hospitalizations (P=0.039) between low and high MCS1 groups. There were no significant confounders.Conclusion: Low MCS scores 1 month after a minor health crisis appear to significantly predict downstream FD. This finding needs to be tested in a larger sample. Keywords: instrumental activities of daily living, mental quality of life, functional decline, falls, hospitalization